TRANSFORMASI CHARNESS AND COOPER PADA LINEAR FRACTIONAL PROGRAMMING DAN PENYELESAIAN DENGAN MENGGUNAKAN METODE CRISS-CROSS - TASTRAWATI, NI KETUT TARI; JULIARTINI, NI LUH EKA; UTARI, IDA AYU PUTU ARI (E-Jurnal Matematika; Vol 14 No 2 (2025)DO - 10.24843/MTK.2025.v14.i02.p480, 2025)
Linear fractional programming is a class of non-linear programming problems with an objective function in the form of a ratio or comparison. The solution used is the Charnes and Cooper transformation to transform linear fractional programming problems into linear programming problems. This paper applies the Charnes and Cooper transformation to  convert such problems into equivalent linear programming models , the solution is continued using the criss-cross method to obtain the optimal solution. This research uses a case study on a convection company and with the research objective is to maximize company profits by comparing selling prices with production capital. Based on the results of the study, a profit of Rp. 134,264,449 was obtained when producing 1.865 medical uniforms, 3.416 PDH, 71 organizations jackets, 124 polo endek shirts, 617 endek shirts .